THE CORRELATION BETWEEN WATER, SANITATION, AND HYGIENE WITH SOIL-TRANSMITTED HELMINTHS INFECTION AMONG ELEMENTARY SCHOOL CHILDREN OF ARU ISLANDS DISTRICT, MALUKU - Tiffany Konstantin; Indah Setyawati Tantular; Alpha Fardah Athiyyah; Lynda Rossyanti (The Indonesian Journal of Public Health, 2021)
ABSTRACTSoil-Transmitted Helminths (STH) infection is the most common intestinal parasite infection in Indonesia. STH infection can interfere with child development and cause cognitive impairment in severe cases.  The school-age group is the most susceptible to STH infection because of direct contact with soil in the school yard. STH infection incidence can be avoided by adequate water, healthy latrines, and good hygiene and can be improved by proper interventions. This study aimed to analyze the correlation between Water, Sanitation, and Hygiene (WASH) with STH infection in Aru Islands District, Maluku. This study used a cross-sectional design and was conducted in Elementary Schools in Karangguli and Wokam villages, Aru Islands district, Maluku. One hundred and six stool samples were collected from both villages. The sociodemographic and WASH data were collected using the interview method. Stool samples were collected and examined for STH infection using a direct smear technique on the light microscope. Data statistical analysis was performed by the SPSS program using the Chi-square or Fischer’s Exact test. The examination results showed that 73 students (68.9%) were infected with STH. The bivariate analysis showed that water source (p = 0.000002), defecation place (p = 0.002), and washing hands after defecation (p = 0.048) were all significantly correlated with STH infection. This study concluded that WASH variables which were water source, defecation place, and washing hands after defecation had a significant correlation with STH infection. Keywords: Water, Sanitation, and Hygiene (WASH); soil-transmitted helminths infection; elementary school students.